Does a mother's childbirth experience influence her perceptions of her baby's behaviour? A qualitative interview study. - Carmen Power; Claire Williams; Amy Brown (PLoS ONE, 2023)
Background Childbirth has become increasingly medicalised, which may impact on the mother's birth experience and her newborn infant's physiology and behaviour. Although associations have been found between a mother's subjective birth experience and her baby's temperament, there is limited qualitative evidence around how and why this may occur. Objectives This qualitative study aimed to explore mothers' childbirth and postnatal experiences, perceptions of their baby's early behavioural style, and whether they saw these as related. Methods A qualitative semi-structured interview schedule collected rich in-depth data. Twenty-two healthy mothers over 18 years of age and with healthy infants aged 0-12 months born at term, were recruited from Southwest regions of England and Wales. Thematic analysis was performed on the data. Results Mothers experienced childbirth as a momentous physical and psychological process. However, they did not necessarily perceive the birth as affecting their baby's early behaviour or temperament. While some mothers drew a direct relationship, such as linking a straightforward birth to a calm infant, others did not make an explicit connection, especially those who experienced a challenging birth and postnatal period. Nevertheless, mothers who had a difficult or medicalised birth sometimes reported unsettled infant behaviour. It is possible that mothers who feel anxious or depressed after a challenging birth, or those without a good support network, may simply perceive their infant as more unsettled. Equally, mothers who have been well-supported and experienced an easier birth could be more likely to perceive their baby as easier to care for. Conclusions Childbirth is a physical and psychological event that may affect mother-infant wellbeing and influence maternal perceptions of early infant temperament. The present findings add to prior evidence, reinforcing the importance of providing good physical and emotional support during and after childbirth to encourage positive mother-infant outcomes.